Electrostatic manipulation for saturated charging and orientating of recycled short-chopped carbon fibers based on dielectric polarization. (20th December 2022) - Fu, Yihan; Tian, Yu; Li, Mengze; Ma, Jiahe; Li, Shuran; Zhu, Weidong; Yan, Keping; Ke, Yinglin
Abstract: Carbon fiber composites produce a large amount of scrap during their life cycle, to recycle and fully utilize these short-chopped carbon fibers (SCFs), present work proposes a method to disperse agglomerated SCFs using pure electrostatic forces, while using dielectric polarization to recycle and emit SCFs. SCFs are disorderly distributed or agglomerated into pellets in their natural state, and they need to be sufficiently charged and oriented for reliable collection. A novel plate-plate structure is proposed to maintain a higher load voltage to disperse and emit a larger amount of SCFs. The charging and orientation mechanisms of SCFs were investigated with high-speed camera. The dispersive characteristics of SCFs were statistically evaluated with Ripley's K function and Two-point spatial correlation. And SCFs were emitted by two different modes and the effects of embedment were studied. The results show that large-scale SCFs can be uniformly dispersed and sufficiently charged to 2 × 10 −2 C/kg in the electrostatic field and oriented to move under the driving of dielectric polarization. Moreover, the direction of embedded SCFs can be well controlled. This study describes the behavior pattern and motion characteristics of SCFs in the electrostatic field and provides a new method for the pollution-free, low-cost, efficient recycling of recycled fibers. It has broad application prospects in the field of carbon fiber reinforced polymer composites and is also significant for the pure electrostatic cross-scale control of micron-sized objects. Graphical abstract: Image 1 Highlights: A novel plate-plate structure is designed to recycle short-chopped carbon fibers. Uniform dispersion of agglomerated fibers using an electrostatic field. Fibers are charged to 2 × 10 −2 C/kg and directionally embedded into the substrate. Structure has better dispersion performance with the ZrO2 dielectric layer. Fibers were embedded into various types of targets using two different modes.